Cooperative learning in science classes in the United Arab Emirates: Learning environment, attitudes, motivation, engagement and career aspirations - Khalil, Nadine (Curtin University, 2015)
The study reported in this thesis examined students’ and teachers’ perspectives on the use of cooperative learning in science classrooms in Abu Dhabi, UAE. The study involved a multistrand, mixed methods approach. Quantitative data was collected to assess students’ (N=784) perceptions of the learning environment, attitudes, motivation and career aspirations in science. Qualitative information was gathered from seven case study teachers. The findings indicated that cooperative learning could lead to improved student outcomes in science.